Neurochemical dementia diagnostics: Assays in CSF and blood - Lewczuk, Piotr; Hornegger, Joachim; Zimmermann, Rüdiger; Otto, Markus; Wiltfang, Jens; Kornhuber, Johannes (European archives of psychiatry and clinical neuroscience, 2008)
In this review, current neurochemical dementia diagnostics (NDD) procedures are presented with a focus on biomarkers in the cerebrospinal fluid (CSF) and blood: amyloid β peptides, tau protein, and its phosphorylated form (pTau). CSF analysis is an increasingly important tool for early and differential diagnosis of dementia syndromes. Although lumbar puncture is a mildly invasive procedure with a low incidence of complications, establishing blood assays capable of reliably measuring NDD biomarkers is an aim of several studies worldwide. © 2008 Springer.